Emotion Reactivity and Suicide Risk in Patients With Depression: The Mediating Role of Non-Suicidal Self-Injury and Moderating Role of Childhood Neglect - Wang, Lu; Cui, Qian; Liu, Jun; Zou, Haiou (Frontiers in Psychiatry, 2021)
Background: The association between emotion reactivity (ER) and suicide risk has been confirmed in recent studies, especially in patients with depression. However, there is a lack of understanding of the underlying mechanism of the relation from ER to suicide risk among patients with depression. This study planned to examine a model of how ER, nonsuicidal self-injury (NSSI) and childhood neglect (CN) interact to affect suicide risk in depressed patients. Methods: 496 patients (64.5% female, mean age = 30.40 years, SD = 12.56) who have accomplished self-rating instruments of ER, NSSI, CN and suicide risk were included. Results: Findings showed that ER was positively connected with suicide risk, and NSSI partially mediated the above connection. Besides, CN moderated the mediation model, that is, the mediation effect was more pronounced in depressed patients with CN compared to depressed patients without CN. Conclusions: It was concluded that there is a relationship among ER, NSSI, CN and suicide risk in patients with depression, and strengthen our knowledge of the mechanism behind suicide risk. Our findings emphasize that the identification of NSSI and CN should be considered when assessing the suicide risk of patients with depression, as well as the intervention focus on emotion regulation and support for patients.